Application of a model-driven simultaneous prestack inversion of rock physical properties in ultra-deep Ordovician carbonate reservoirs in the Shunbei area - Wang, Zhiwei; Fu, Li-Yun; Jian, Shikai; Deng, Wubing (Frontiers in Earth Science, 2023)
Synchronous prestack inversion technology has been widely used to predict the fluids and lithological properties of reservoirs. Its prediction accuracy depends on the seismic data quality. The ultra-deep carbonate reservoirs in the Shunbei area of the Tarim Basin were used as research objects. Based on the shear wave (S-wave) prediction method, petrophysical logging analysis was carried out to select the physical property-sensitive elastic parameters. A physical property indicator with porosity as the target curve was constructed to quantitatively characterize the differences in physical properties in this area. The signal-to-noise ratio (SNR) and resolution of the dataset were improved by preprocessing the seismic and logging data. P- and S-wave impedances and densities obtained from prestack synchronous inversion, which integrate the physical property indicator model, spatial distribution, and transverse variation of the physical parameters of the Ordovician carbonate reservoirs are described. The planar distribution of reservoirs can be effectively predicted.